Lumacaftor/ivacaftor changes the lung microbiome and metabolome in cystic fibrosis patients. Issue 2 (19th April 2021) - Neerincx, Anne H.; Whiteson, Katrine; Phan, Joann L.; Brinkman, Paul; Abdel-Aziz, Mahmoud I.; Weersink, Els J.M.; Altenburg, Josje; Majoor, Christof J.; Maitland-van der Zee, Anke H.; Bos, Lieuwe D.J.
Rationale: Targeted cystic fibrosis (CF) therapy with lumacaftor/ivacaftor partly restores chloride channel function and improves epithelial fluid transport in the airways. Consequently, changes may occur in the microbiome, which is adapted to CF lungs. Objectives: To investigate the effects of lumacaftor/ivacaftor on respiratory microbial composition and microbial metabolic activity by repeatedly sampling the lower respiratory tract. Methods: This was a single-centre longitudinal observational cohort study in adult CF patients with a homozygous Phe508del mutation. Lung function measurements and microbial cultures of sputum were performed as part of routine care. An oral and nasal wash, and a breath sample, were collected before and every 3 months after starting therapy, for up to 12 months. Results: Twenty patients were included in this study. Amplicon 16S RNA and metagenomics sequencing revealed that Pseudomonas aeruginosa was most abundant in sputum and seemed to decrease after 6 months of treatment, although this did not reach statistical significance after correction for multiple testing. Two types of untargeted metabolomics analyses in sputum showed a change in metabolic composition between 3 and 9 months that almost returned to baseline levels after 12 months of treatment. The volatile metabolic composition of breath was significantly different after 3 months and remained different from baseline until 12 months follow-up. Conclusions: After starting CF transmembrane conductance regulator (CFTR) modulating treatment in CF patients with a homozygous Phe508del mutation, a temporary and moderate change in the lung microbiome is observed, which is mainly characterised by a reduction in the relative abundance of Pseudomonas aeruginosa . Lumacaftor/ivacaftor in adult cystic fibrosis patients with homozygous Phe508del results in temporal and moderate changes in lung microbiome and metabolome, that are mainly characterised by a reduction in the relative abundance of Pseudomonas aeruginosa https://bit.ly/3pcPUfX